Ecophysiological Performance of Proteaceae Species From Southern South America Growing on Substrates Derived From Young Volcanic Materials - Delgado, M.; Zúñiga-Feest, A.; Reyes-Díaz, M.; Barra, P. J.; Ruiz, S.; Bertin-Benavides, A.; Valle, S.; Pereira, M.; Lambers, H. (Frontiers in Plant Science, 2021)
Southern South American Proteaceae thrive on young volcanic substrates, which are extremely low in plant-available phosphorus (P). Most Proteaceae exhibit a nutrient-acquisition strategy based on the release of carboxylates from specialized roots, named cluster roots (CR). Some Proteaceae have a colonizing ability, which has been related to CR functioning. However, physiological functioning of other Proteaceae to thrive on recent volcanic substrates is unknown. We conducted an experiment with seedlings of five Proteaceae (Gevuina avellana, Embothrium coccineum, Lomatia hirsuta, L. ferruginea and L. dentata) grown in three volcanic materials. Two of them are substrates with very low nutrient concentrations, collected from the most recent deposits of the volcanoes Choshuenco and Calbuco (Chile). The other volcanic material corresponds to a developed soil that exhibits a high nutrient availability. We assessed morphological responses (i.e. height, biomass and CR formation), leaf nutrients concentrations and carboxylates exuded by roots. The results showed that in young volcanic substrates, G. avellana and E. coccineum presented the greatest height, biomass and leaf P concentration compared with Lomatia species. Gevuina avellana presented the greatest CR biomass and carboxylate-exudation rate (mainly succinate), whereas Lomatia species allocated less biomass to CR and exuded only oxalate. Embothrium coccineum had more CR biomass than the Lomatia species, but exuded carboxylates at a slower rate than Lomatia, probably because at the time of the harvest (autumn), most CR had already senesced in E. coccineum. We conclude that Proteaceae from temperate rainforests differ in their ability to grow and acquire nutrients in young and nutrient-poor volcanic substrates. The greater total plant biomass, leaf P concentration and faster carboxylate exudation (only for G. avellana) helps explain why G. avellana and E. coccineum are better colonizers of recent volcanic substrates than Lomatia species.